Direct-to-consumer mobile teledermoscopy for skin cancer screening: Preliminary results demonstrating willingness-to-pay in Australia. (December 2018) - Snoswell, Centaine L; Whitty, Jennifer A; Caffery, Liam J; Loescher, Lois J; Gillespie, Nicole; Janda, Monika
Introduction: Internationally, teledermoscopy has been found to have clinical and economic efficacy. This study aims to identify the attributes of a mobile teledermoscopy service that consumers prefer. This preliminary study was set within a broader randomised control trial (RCT) investigating the effectiveness of direct to consumer mobile teledermoscopy. Methods: We undertook a discrete choice experiment (DCE). The DCE comprised 24 choice sets, divided into in two blocks of 12. For each choice set, respondents were asked to make discrete choices between two opt-out choices and two skin cancer screening service options described by seven attributes. A mixed logit model was used to estimate preferences for skin cancer screening services. Consumer preferences weights were used to calculate marginal willingness-to-pay (WTP) for skin cancer screening services. Results: The DCE was completed by 113 consumer respondents. Consumers' preference for dermatologist involvement in their diagnosis, increased accuracy, and reduced excisions were all statistically significant in driving choice between service models. Consumers preferred having a professional involved in their skin cancer screening, rather than performing a self-examination. Consumers were only WTP $1.18 to change from a GP visit to mobile teledermoscopy (diagnosis using a phone camera). However, they were WTP $43 to have their results reviewed by a dermatologist rather than a GP, and $117 to increase the chance of detecting a melanoma if it was present from 65-75% to 95%. Conclusion: Skin cancer screening services which are delivered by health professionals, rather than skin self-examination, are preferred by consumers. Consumers were willing to pay for their preferred skin cancer screening method, especially if a dermatologist was involved.